Efecto de la fitasa en el aprovechamiento del fósforo en dietas para tilapia (Oreochromis niloticus). Resultados preliminares (ING) - Günther, Jorge; Jiménez, Ricardo; Vargas, William (Uniciencia, 2001)
The aim of this study was to test if the inclusion of bacterial phytase in tilapia diets would reduce the requirement of dietary phosphorous for tilapia (Oreochromis niloticus). Four diets (0,8% P, 0,5% P, 0,5% P with 600 FTU phytase and 0,5% P with 1,200 FTU phytase) were tested in a 6 week experiment with juvenile Oreochromis niloticus. Inclusion of phytase improved growth and feed conversion, and with 1,200 FTU phytase growth and feed conversion were even superior to the diet with high phosphorous, but the results were statistically not significant. Excretion of phosphorous into the water and the faeces were significantly reduced through phytase inclusion. The advantages of phytase inclusion for various aspects of intensive fish culture are discussed.